Mental illness and health-seeking of adults and children: A critical ethnography of Karamoja, north-eastern Uganda - Byanasaye, James Wasike Mangeni (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.